MENGGALI POTENSI STRATEGI INFLUENCER UNTUK MEMBANGUN CITRA YANG BERKELANJUTAN - Muhammad Satrio Juliyanto (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
As social media influencers are considered to have a significant impact on society, many businesses and organizations have been promoting the use of influencers, especially micro-influencers, who can reach and even influence hard-to-reach audiences such as special interest groups. Influencers are also considered to have the ability to mediate messages quickly and efficiently, which increases the likelihood of the message going viral and impacting many people in addition to the community. The researcher used a constructivist paradigm, qualitative methods, and descriptive research to provide an overview of how influencers are used on social media, specifically Instagram, how they package messages or content, and how much impact they have as a public relations tactic in the digital age. The research and data collection were conducted through collecting data through journals, which specifically fall under the category of micro-influencers on Instagram social media. In addition, the researcher also made observations of the two influencers' Instagram social media accounts and their interactions with their followers. The results showed that micro-influencers are seen as effective and have had an impact in influencing their followers on social media. Personalization, engagement and authentic relationships between micro-influencers and their followers are factors in building trust that brings influence over the messages delivered by micro-influencers.